Women in banking : continuity and change since the second world war - Crompton, Rosemary [Verfasser] (My University, 1989)
"Employment relations in the major clearing banks have been the subject of sociological attention since the 1950s, when they presented the apparent epitome of the bureaucratic career. However, the banks have increasingly become major employers of female labour. Women in banks have not historically had the same career oppurtunities as men, for a variety of reasons ranging from deliberate male exlusion practices to the broken and often short- term nature of many women's work histories. This contrast between the experiences of men and women in the same occupation is used to question the 'conventional view' of occupational class analysis, where the (male) occupational structure is treated as if it were the 'class structure'. The argument is developed using a number of sources, including the occupational history of a female bank employee with over thirty years work experience, as well as the findings of recent equal opportunities investigations." (author's abstract) ((en)) Der Beitrag befasst sich mit der beruflichen Situation von Frauen im Bankensektor Grossbritanniens seit den 50er Jahren. Dabei wird der Frage nachgegangen, ob bisherige Annahmen zur Entwicklung der Beschäftigtenstruktur zu sehr unter dem Blickwinkel männlicher Berufsverläufe getroffen wurden. Die Argumentation wird u.a. durch ein qualitatives Interview mit einer Bankangestellten über deren Arbeitsleben gestützt. (IAB)
Frauen im Bankgewerbe. Kontinuität und Wandel seit dem 2. Weltkrieg
Keywords: G 1.2.4.2.4 Kredit und Versicherung; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; P 1.3 Frauen; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; Frauen; Bankgewerbe; Geschlechtsspezifische Faktoren; Berufsverlauf; Frauenerwerbstätigkeit; Entwicklung; 1950-1986